Differential impacts of vaccination on wildlife disease spread during epizootic and enzootic phases. Issue 3 (8th February 2019) - Newton, Erica J.; Pond, Bruce A.; Tinline, Rowland R.; Middel, Kevin; Bélanger, Denise; Rees, Erin E.
Abstract: Dissemination of oral vaccine baits is a cost‐effective method to contain and control infectious wildlife diseases. The effectiveness of vaccine barriers in slowing or halting disease spread depends on host ecology and landscape variability. However, it is not clear the extent to which the success of vaccine barriers to manage disease may change from an epizootic to an enzootic phase of a disease invasion, nor is it apparent if this depends on the quality and configuration of host habitats. We explore these questions using the raccoon variant rabies virus (RRV) as a model system. This zoonotic disease of high concern has been enzootic in eastern North America for decades, pushing into new areas and re‐emerging in previously controlled zones. We use a spatially explicit individual‐based model to assess how levels of oral vaccination and habitat fragmentation affect RRV spread across vaccine barriers during epizootic and enzootic phases. We use space‐time characteristics of infection chains (individual‐to‐individual transmission of RRV) to compare simulated outcomes. Results indicate that vaccine barriers have the strongest impact on the control of RRV during the epizootic phase. Counterproductively, mid‐levels of immunisation during an enzootic phase lead to more rabies‐induced mortalities than lower or higher vaccination levels. Infection chains spread faster during the epizootic phase. Landscape effects on chain characteristics were more subtle than effects of invasion phase and vaccination. Synthesis and applications . A spatially explicit individual‐based modelling approach to examine mechanisms of raccoon variant rabies virus spread during epizootic and enzootic phases provides insights into efficacy of wildlife disease vaccination efforts. Our results demonstrate the importance of detecting and controlling outbreaks before they become enzootic. We discuss the implications for moving vaccine barriers to push back and decrease the size of enzootic areas. Abstract : A spatially explicit individual‐based modelling approach to examine mechanisms of raccoon variant rabies virus spread during epizootic and enzootic phases provides insights into efficacy of wildlife disease vaccination efforts. Our results demonstrate the importance of detecting and controlling outbreaks before they become enzootic. We discuss the implications for moving vaccine barriers to push back and decrease the size of enzootic areas.